Model Penghimpunan Dana Zakat Infak Sedekah Yang Efektif Dan Efisien Di Era Digital - Rusman, Rusman; Amrizal, Amrizal (Jurnal Ilmiah Ekonomi Islam, 2024)
Baitul Maal Hidayatullah (BMH) is an institution that received permission to manage zakat infaq, alms, and humanitarian funds. In its management, BMH Kaltim Representatives are managed by appointed amil without special criteria. This study aims to analyze effective and efficient collection models in the digital era. Research is expected to provide knowledge about effective and efficient collection models in the digital era. This research is qualitative descriptive research with data analysis using NVIVO 12 PLUS. Based on the results of field findings, it is known that the collection model in BMH is a variety of models, this adjusts to the choice of people who pay infaq zakat and alms through BMH. Effective and efficient in the digital era in BMH can be seen from the acquisition of BMH which has increased with the lack of operations spent to achieve it.